Wastewater Treatment Using Green Technology - Wanjohi , L.; Mwamburi , L.; Mwasi , S. (African Journal of Education,Science and Technology (AJEST), 2019)
Water is a vital, indispensable resource which organisms require for the sustenance of life. Currently, problem of water scarcity persists due to water pollution by heavy metals and eutrophic nutrients that have resulted in degraded environment and adverse effects on biota. Conventional methods are employed to remove heavy metals from wastewater but are un-economical especially while the metals are in low but significant concentration. Alternative method is phytoremediation which effectively removes pollutants from environments. This research was carried out to establish the ability of macrophytes to remediate pollutants from wastewater. Locally available macrophytes which included Azolla pinnata, Typha latifolia, Nymphaea spp. and Ceratophyllum demersum were collected from Marura wetland and identified. Wastewater samples were collected from University of Eldoret sewage treatment plant. Water indicator parameters, nutrients and heavy metals were determined using standard methods. Growth chambers containing wastewater samples were prepared in the laboratory. Macrophytes were established in these chambers. Wastewater analysis was carried out initially on setting up the experiment and then after every five days for 25 days to determine the changes in the levels of the parameters investigated. Means of mentioned parameters were calculated and analyzed using ANOVA and significant means separated using Tukey’s test at 5% level. Reduction efficiency was calculated. The range of removal efficiency of the investigated parameters was as follows; TDS 66.01-74.03%, pH 18.15-20.30%, conductivity 51.79-57.11%, turbidity 67.55-86.10%, faecal coliforms 100%, phosphates 88.65-100%, nitrates 89.38-100%, cadmium 88.96-92.19%, copper 78.87-85.86%, nickel 100%, cobalt 94.67-95.04%, lead 100%, manganese 85.81-88.81%, zinc 91.78- 93.64% and iron 85.81-88.81%. There were significant differences in reduction of phosphates, nitrates, lead and cadmium among the macrophytes, (P = 0.00). The macrophytes were found to be efficient in wastewater treatment. The order of removal efﬁciency was Azolla pinnata > Nymphaea spp > Typha latifolia > Ceratophyllum demersum. These macrophytes can be used to treat domestic, agricultural and industrial wastewater.